HUBUNGAN ANTARA MASA KERJA DENGAN KADAR TIMBAL (Pb) DALAM DARAH PADA PEKERJA INDUSTRI PENGECORAN LOGAM CV. BONJOR JAYA DI DESA BATUR, CEPER, KLATEN - Dian Islamiari Qoriah; Onny Setiani; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Lead is a toxic substance that has cumulative effect and harmful to human health. Metal foundry is a metal industry that has the potential contributes pollutants lead into the air. So that workers in the foundry including people at risk of exposure metallic lead, because the raw materials used metal may contain lead. Purpose of this research is to determine the relationship between working period and lead concentration in blood at the metal foundry industry workers CV. BonjorJaya in Batur, Ceper, Klaten. The research method used analytical observation with cross sectional design. Total of samples are 31 people with purposive sampling. Analysis of data, the writer used Chi Square test with a significance level of 0,05 and 95% confidence level. The results were obtained concentration Pb in the air parts of the foundry are 0,208 mg/Nm3, printing are 0,212 mg/Nm3 and finishing are 0,037 mg/Nm3. Mean lead concentration in blood of the workers was 14,38 µg/dL with minimum concentration of 3,00 µg/dL, maximum of 37,40 µg/dL. Mean working period was 10,11 years with the most recent of working period one year and the longest 28 years. As many as 51,6% of workers had Pb concentration in blood above normal (>10 µg/dL). Based on the results of statistical tests showed that there was no relationship between working period and lead concentration in blood at the metal foundry industry workers CV. Jaya Bonjor in Batur, Ceper, Klaten (p value = 1,000). Suggestion for the company, monitoring work environment about air quality especially lead and held a medical checks for workers in periodic, establish policy about limitation of working period and job site and use of Personal Protective Equipment. For workers suggested obligatory use of PPE and pay attention personal hygiene in the workplace.